Vanekovo stoletje: ob 100. letnici rojstva dr. Vaneka Šiftarja (University of Maribor Press, 2019)
Vanek’s Century: On the Centenary of the Birth of Vanek Šiftar. The monograph, which comprises thirty-five scientific and professional papers, was published on the occasion of the centenary of the birth of dr. Vanek Šiftar and is in essence the third so-called Vanek’s proceedings. The first part of the monograph contains commemorative contributions that illuminate the life and various fields of activity of three important and associated Prekmurje Slovenes - Vanek Šiftar, his companion Anton Vratuša, and Franco Kuzmič, who passed away last year. The second part comprises professional and scientific papers, thematically broadly related to Prekmurje and/or the work of Vanek Šiftar and Anton Vratuša. The third part consists of scientific contributions that deal with different fields of research of Vanek Šiftar, and partly also of Vratuša and Kuzmič, ranging from law (constitutional, labour), history, linguistics, to human rights, patriotism, social responsibility and the humanities in the broadest sense.